Prevalence and Risk Factors of Carotid Plaque Among Middle-aged and Elderly Adults in Rural Tianjin, China - Zhan, Changqing (Sci Rep, 2016)
Carotid plaque (CP) is associated with cardiovascular and cerebrovascular events. However, population-based studies with a large sample are rare in China, particularly those in the low-income population. We aimed to determine the prevalence of CP and the associated risk factors in the rural areas of northern China. Between April 2014 and June 2014, we recruited 3789 residents aged ≥45 years. B-mode ultrasonography was performed to measure the extent of CP. The prevalence of CP was 40.3% overall, 47.1% in men, and 35.4% in women (P < 0.001). The prevalence of CP increased with increasing age (P < 0.001). The participants with CP were more likely to have hypertension, diabetes, high total cholesterol (TC) levels, and high low-density lipoprotein-cholesterol levels and be a current smoker; however, they were less likely to be obese. Multiple logistic regression analysis, adjusted for confounders, indicated that age, male sex, hypertension, diabetes, current smoking, and high LDL-C levels were the independent risk factors for CP. There was a lower risk of CP with alcohol consumption. The findings suggest that managing the conventional risk factors is crucial to reduce the burden of cardiovascular and cerebrovascular diseases in the low-income population in China.